(How) do the ECB and the fed react to financial market uncertainty? The Taylor rule in times of crisis - Ansgar Belke; Jens Klose (Research On Money in the Economy (ROME), 2010)
We assess differences that emerge in Taylor rule estimations for the Fed and the ECB before and after the start of the subprime crisis. For this purpose, we apply an explicit estimate of the equilibrium real interest rate and of potential output in order to account for variations within these variables over time. We argue that measures of money and credit growth, interest rate spreads and asset price infl ation should be added to the classical Taylor rule because these variables are proxies of a change in the equilibrium interest rate and are, thus, also likely to have played a major role in setting policy rates during the crisis. Our empirical results gained from a state-space model and GMM estimations reveal that, as far as the Fed is concerned, the impact of consumer price inflation, and money and credit growth turns negative during the crisis while the sign of the asset price inflation coefficient turns positive. Thus we are able to establish significant differences in the parameters of the reaction functions of the Fed before and after the start of the subprime crisis. In case of the ECB, there is no evidence of a change in signs. Instead, the positive reaction to credit growth, consumer and house price inflation becomes even stronger than before. Moreover we find evidence of a less inertial policy of both the Fed and the ECB during the crisis.
Keywords: E43; E52; E58; 330; Subprime crisis; Federal Reserve; European Central Bank; equilibrium real interest rate; Taylor rule